2014
DOI: 10.4103/0019-509x.151989
|View full text |Cite
|
Sign up to set email alerts
|

Submucosal tunneling endoscopic resection for upper gastrointestinal multiple submucosal tumors originating from the muscular propria layer: A feasibility study

Abstract: Submucosal tunneling endoscopic resection is a safe and efficient technique for treating multiple esophageal SMTs originating from MP layer, which can avoid patients suffering repeated resections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 22 publications
(24 reference statements)
0
8
0
Order By: Relevance
“…Hence, only the study [14] with the longer time interval was included in our review and the other study [24] was excluded to avoid duplication of data. Of the remaining 16 studies, three were case reports [13,16,22], nine were retrospective studies [8,11,12,14,15,17-19,21] and four were prospective studies [9,10,20,23]. All studies except two [16,23] were conducted in China [8-15,17-22], which could have led to bias in our results.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, only the study [14] with the longer time interval was included in our review and the other study [24] was excluded to avoid duplication of data. Of the remaining 16 studies, three were case reports [13,16,22], nine were retrospective studies [8,11,12,14,15,17-19,21] and four were prospective studies [9,10,20,23]. All studies except two [16,23] were conducted in China [8-15,17-22], which could have led to bias in our results.…”
Section: Resultsmentioning
confidence: 99%
“…The mean hospital duration for studies including all tumors, irrespective of their location, varied from 3.2-5.4 days [9,11,12,14]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All tumors were resected successfully, the mean procedural time was 49.0 minutes, which was comparable to other studies (range, 40 to 78.3 minutes). 12 15 Due to the large size (40 mm), three esophageal tumors were piecemeal resected. There may be a concern whether piecemeal resection could result into the recurrence of tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al . 15 expanded this experience, and applied ESTD for treating 23 patients with 49 multiple SMTs from MP layer in upper GI tract. They reported that all the SMTs were resected completely by ESTD technique, and the complications was managed conservatively.…”
Section: Discussionmentioning
confidence: 99%